Integration of Digital Media in English Learning to Increase Active Participation of High School Students - Purwanita, Kadek Agina (Journal of Educational Study, 2024)
This study aims to describe how digital media integration can increase the active participation of senior high school students in English learning in Bali Province. This study uses a descriptive qualitative approach based on literature studies, with data sources in the form of relevant national and international journals in the last five years. The results of the study indicate that digital media such as interactive videos, mobile learning applications, and learning management platforms are able to create more interesting and collaborative learning spaces. Active student participation is still low due to limited teacher skills in designing digital learning and lack of support for school infrastructure and policies. Digital media integration becomes effective when combined with flipped classroom strategies, technology-based collaborative projects, and ongoing formative assessments. Thus, digital media has great potential to encourage student engagement cognitively, affectively, and behaviorally when integrated with pedagogical designs that are contextual and adaptive to the learning culture of students in Bali.